Digital transformation, green innovation, and audit fees - Lou, Pengzhen; Zhou, Xiaohui (Frontiers in Environmental Science, 2024)
Under the trend of synergistic development of digitalization and greening, this paper investigates the impact of enterprise digital transformation on audit fees and its mechanism, by using textual analysis and performing empirical tests on the data of Chinese listed companies from 2007 to 2021. It is found that enterprise digital transformation significantly increases audit fees, and green innovation partially mediates this process. The study results are robust, even after a series of robustness tests. When financing constraints and environmental regulations are low, the mediating role of green innovation between digital transformation and audit fees is more significant. In addition, green innovation has a stronger mediating role between the use of underlying technology and audit fees, while green substantive innovation has a stronger mediating role between digital transformation and audit fees. This study investigates the effect of enterprise digital transformation on audit fees from the standpoint of green innovation. It offers a new perspective on how accounting firms make audit pricing decisions, provides guidance for enterprise digital transformation and green innovation, and gives an opportunity for China to promote the synergistic transformation and development of digitalization and greening to achieve the dual-carbon goal.